Educational Integration of People with Special Needs: A Socio-Educational Reading - AMIRECHE, Nadjoua (Journal of Human Sciences, 2024)
The attention to individuals with special needs has become a crucial demand among the advancements and comprehensive development of modern societies, which are characterized by changes and evolutions in general life concepts, especially within the educational system. A modern trend has emerged, advocating for the inclusion of disabled individuals in regular schools and recognizing their rights to a normal school life alongside their non-disabled peers, moving away from the isolation system long adopted by special education. Within this context, the research paper aims to explore the school integration process for individuals with special needs by defining the concept of school integration, its goals, the expected benefits thereof, the essential conditions for successful integration, and combating the isolation of people with special needs.